2010
DOI: 10.1017/s003358351000017x
|View full text |Cite
|
Sign up to set email alerts
|

The sarcoplasmic Ca2+-ATPase: design of a perfect chemi-osmotic pump

Abstract: The sarcoplasmic (SERCA 1a) Ca2+-ATPase is a membrane protein abundantly present in skeletal muscles where it functions as an indispensable component of the excitation-contraction coupling, being at the expense of ATP hydrolysis involved in Ca2+/H+ exchange with a high thermodynamic efficiency across the sarcoplasmic reticulum membrane. The transporter serves as a prototype of a whole family of cation transporters, the P-type ATPases, which in addition to Ca2+ transporting proteins count Na+, K+-ATPase and H+,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
272
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 271 publications
(278 citation statements)
references
References 272 publications
4
272
1
1
Order By: Relevance
“…On the basis of amino acid sequence alignment, the P4-ATPases are predicted to structurally resemble the classic P-type ATPase cation pumps Na + ,K + -ATPase and Ca 2+ -ATPase, possessing a transmembrane domain with 10 helices (M1-M10) and three cytoplasmic domains, P (phosphorylation), N (nucleotide binding), and A (actuator) (Fig. 1A), known from crystal structures to undergo large movements during the catalytic cycle (8,9). Recently, we showed that the P4-ATPase ATP8A2, like the cation pumps, forms an aspartyl-phosphorylated intermediate and undergoes a catalytic cycle involving the conformations E 1 , E 1 P, E 2 P, and E 2 similar to the Post-Albers scheme originally proposed for the Na + ,K + -ATPase ( Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of amino acid sequence alignment, the P4-ATPases are predicted to structurally resemble the classic P-type ATPase cation pumps Na + ,K + -ATPase and Ca 2+ -ATPase, possessing a transmembrane domain with 10 helices (M1-M10) and three cytoplasmic domains, P (phosphorylation), N (nucleotide binding), and A (actuator) (Fig. 1A), known from crystal structures to undergo large movements during the catalytic cycle (8,9). Recently, we showed that the P4-ATPase ATP8A2, like the cation pumps, forms an aspartyl-phosphorylated intermediate and undergoes a catalytic cycle involving the conformations E 1 , E 1 P, E 2 P, and E 2 similar to the Post-Albers scheme originally proposed for the Na + ,K + -ATPase ( Fig.…”
mentioning
confidence: 99%
“…In the welldocumented catalytic cycles of Na + ,K + -ATPase and Ca 2+ -ATPase, the glutamate of M4 binds Na + /K + and Ca 2+ /H + and is alternately exposed to the two sides of the membrane during the cycle (9,17,18). Mutations of nearby located residues in M4 have been shown to block the E 1 P→E 2 P or E 2 P→E 2 transition (19)(20)(21).…”
mentioning
confidence: 99%
“…If alternative hydrogen bonding patterns provide low-energy pathways for helix bending that are accessible by thermal motions, we might also expect to see hydrogen bond shifts during the conformational changes that occur in catalytic cycles. We therefore examined the backbone hydrogen bonding patterns that occur in the sarcoplasmic Ca 2þ -ATPase, for which there are many structures representing distinct stages in the transport cycle (34). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The sulfur-sulfur distance between Met148 and the likely internal receiver, Cys382, is 9.3 Å in the Cu þ -free E2.P i state crystal structure (9), and although both residues showed significant flexibility in the E2.P i simulations, large-scale conformational changes are likely required to enable ion transfer, as observed in other P-type ATPase proteins (70). Therefore, although so far we had relied on the accuracy of the crystal structure, to characterize a putative ion-entry mechanism we had to accept the possible uncertainties of modeling an inward-facing LpCopA E1 state.…”
Section: Discussionmentioning
confidence: 99%